Innovation in Education: A winning transformation tool in the era of the new ICT Revolution - SEKE, MBOUNGOU MOUYABI (IJRDO- Journal of Educational Research, 2017)
ICT-based technologies are the drivers of the current paradigm, which, the author discussed in previous contributions, is still at an early stage of diffusion, particularly for emerging countries. Building from historical evidence, the author argues that catching up of innovative education critically depends on the ability of educators to master the technology behind the dominant techno-economic paradigm and for educational institutions to adapt on the shift of the current paradigm. The author then discusses threats and opportunities related to a possible ICT-based development path.